An introduction to mysticism - Smith, Margaret, 1884-1970. (London Sheldon Press, 1977)
Reprint of the 1931 ed. published by S.P.C.K., London, under title: An introduction to the history of mysticism
Bibliography: p.117-118.
Includes index.
Keywords: Mysticism -- History